(3QSGdI aj eUWdM GdMOjKs - (3eMeO GdSYjO Hf eMjj GdOjf GdMSfj GdLRGFQj,J (B1278 (3g` s ((3YHO GdbGOQ Hf eMeO Hf jYbhH s)
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje hUdi Gddg Ydi SjOfG eMeO heeeG MQQg HYV GdaVdGA GdeTGjN ef eUWdM GdMOjK bhdg GdMOjK gh GSe ef GdJMOjK s
(3BNQgG (B:s
(3Ef cGf VYjakG adGjbGd HUHjZ GdLRe Hd jbGd Qhi Yfg cPG , Ch jQhi Yfg cPG , Ch LGA Yfg cPG Ch jPcQ Ch jMci Ch HdZfG Ch eG CTHg Pdc hGdMeO ddg QH GdYGdejf s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs